The use of LCC method in running cost analysis of a single-family house - Jarosław Ziemski (Economic and Environmental Studies (E&ES), 2018)
In the process of making decisions on building a single-family home, many variables of a cost nature should be taken into consideration, which will affect the total level of costs of use of the building in the long-term perspective. Life Cycle Costing (LCC) is a method that can support this process, which is why the main purpose of this article is to analyze the cost of using a single-family home using the LCC method, taking into account environmental aspects that are important in shaping the quality of life of individual households and local communities. In this context, an answer to the following research problem is sought: How to calculate and reduce the costs of using a single-family home in the perspective of its life cycle, taking into account the current and prospective energy and environmental conditions? In order to accomplish the above research objectives, the first part of the article presents the theoretical basis for calculating the costs of maintaining single-family buildings together with a description of use of the LCC method. Next, a case study was presented, within which the long-term costs of maintaining a single-family building were calculated and the pro-ecological possibilities of their reduction were indicated.
Keywords: O14; O31; O32; 330; product life cycle cost; present value of cash flows; running cost; total cost